1983
DOI: 10.1111/j.1600-0714.1983.tb00346.x
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine‐rich crystals in pleomorphic adenomas of parotid glands

Abstract: Histochemical methods for proteins were applied to crystals found in pleomorphic adenomas of the parotid. Positive reactions were obtained with methods for tyrosine, tryptophan, arginine and sulphydryl groups, and indicate a greater complexity of composition than has previously been acknowledged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Similar crystalline structures were subsequently identified in several pleomorphic adenomas of the parotid by Chaplin et al ,2 who found the structures to include tryptophan, arginine and thiol groups, as well as tyrosine, and regarded them as “tyrosine-rich crystals”. The term “tyrosine-rich crystalloids” was preferred by Gould et al ,3 who showed by electron microscopy that these crystal structures were finely granular and electron-dense but not birefringent and without a solid internal structure.…”
supporting
confidence: 61%
“…Similar crystalline structures were subsequently identified in several pleomorphic adenomas of the parotid by Chaplin et al ,2 who found the structures to include tryptophan, arginine and thiol groups, as well as tyrosine, and regarded them as “tyrosine-rich crystals”. The term “tyrosine-rich crystalloids” was preferred by Gould et al ,3 who showed by electron microscopy that these crystal structures were finely granular and electron-dense but not birefringent and without a solid internal structure.…”
supporting
confidence: 61%
“…5,12,19,24 The reported frequency of these structures as cited in the literature varies from 2% to 21%. 5,10,19 The highest occurrences, occurring among African American patients, are up to 20 times greater than in white patients. 24 All four cases of TRC in this series as well as the two cases with very few TRC on histology were from African American patients (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…2 They are consistently pink in H&E stain, 2,5,6,11 rusty or yellowish in Papanicolaou stain 1,6 and bluish or turquoise with Wright-Giemsa stain. 1,5,12 Classically, TRC are reddish brown with Millon's stain. 2,8,19 Millon's stain and the protein deoxidization coupling reaction are specific procedures for tyrosine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Furthermore, the floret-like crystals lack a recognizable internal structure by electron microscopy, so they are more appropriately termed ''tyrosine-rich crystalloids.'' 5 In contrast, the crystals we described do show regular periodicity by electron microscopy.…”
Section: Dear Dr Bedrossianmentioning
confidence: 99%